2013
DOI: 10.1371/journal.pbio.1001726
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4 Is a Novel Phosphoinositide-Binding Protein Modulating Tight Junctions and Favoring Cell Migration

Abstract: The cancer-associated TRAF4 protein has a TRAF domain that is a bona fide phosphoinositide-binding domain and involved in the modulation of tight junctions and cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 90 publications
1
48
0
1
Order By: Relevance
“…3D). A recent study demonstrated that TRAF4 destabilizes tight junctions (TJs) of malignant mammary epithelial cells (MECs) and increases cell migration for cancer progression via binding to phosphoinositide (PIP) on the intracellular membrane, supporting our finding that TRAF4 is attached to its proper receptor and the intracellular membrane during signaling events (22).…”
Section: Detailed Traf4-gpibβ Interaction Mode and Its Comparison Withsupporting
confidence: 85%
See 1 more Smart Citation
“…3D). A recent study demonstrated that TRAF4 destabilizes tight junctions (TJs) of malignant mammary epithelial cells (MECs) and increases cell migration for cancer progression via binding to phosphoinositide (PIP) on the intracellular membrane, supporting our finding that TRAF4 is attached to its proper receptor and the intracellular membrane during signaling events (22).…”
Section: Detailed Traf4-gpibβ Interaction Mode and Its Comparison Withsupporting
confidence: 85%
“…1B). Although three different groups, including ours, have recently determined the structure of the TRAF4 TRAF domain (21)(22)(23), it is not known how TRAF4 can accommodate various receptors using a limited interaction interface. Interestingly, sequence comparison with other TRAF family members revealed that receptor-interacting hot spots are not conserved in TRAF4, indicating that TRAF4 might use a novel interaction mode for binding with different receptors (Fig.…”
mentioning
confidence: 99%
“…Using lipid overlay assays we showed that recombinant TRAF4 binds all PIPs and phosphatidic acid (PA) through its TRAF domain. 17 Liposome flotation assays, mass spectrometry and isothermal titration calorimetry analyses confirmed this binding and showed that, in solution, the TRAF domain of TRAF4 forms a homotrimer which binds up to 3 PIP molecules. The affinity between one lipid-binding site of the TRAF trimer and one PIP molecule was around 5 mM, which is consistent with the lipid-binding affinity of other TJ-related proteins such as PAR3, Zonula Occludens-1 (ZO-1) and ZO-2.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, TRAF4 is involved in the dynamics of TJs: its expression delays TJ assembly and favors cell migration in mammary epithelial cells (MECs) documenting the important function for this protein during cancer progression. 17 The Cancer Protein TRAF4, a Dynamic Protein from TJ TRAF4 has an unusual cellular localization: it is present in many distinct cellular compartments including the cytoplasm, the nucleus and the plasma membrane. 16,18,19 We have previously documented that in normal human mammary tissues, TRAF4 is mainly localized in epithelial cell TJs and TRAF4 labeling on sections typically appears as a honeycomb pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation